SOME DIFFERENCES BETWEEN BOCCACCIO’S AND CHAUCER’S TALES OF GRISELDA - Reichmann Lemos, Brunilda (Revista Letras, 1981)
This paper tries to demonstrate that Chaucer in his "Tale of Griselde" has used, besides Boccaccio’s tale, Petrarch’s revised verson, as it is found in the Epistolae seniles, Manuscript 1165, and Mézière’s translation as it appears in Le Ménagier de Paris.